Randomized double-blind clinical trial of a new human epoetin versus a commercially available formula for anemia control in patients on hemodialysis (Clinics, 2014)
OBJECTIVES: Anemia is a common complication among chronic kidney disease patients on hemodialysis, occurring mostly due to erythropoietin deficiency. This randomized noninferiority trial sought to compare the efficacy and safety of a new epoetin formulation developed by Bio-Manguinhos, a biologics manufacturer affiliated with the Brazilian government, with those of a commercially available product currently used in Brazil (a biosimilar epoetin formulation). METHODS: The sample size needed to enable demonstration of noninferiority with a statistical power of 85% for a between-group difference in hemoglobin levels of no more than 1.5 g/dL was calculated. In total, 74 patients were randomly assigned to receive the epoetin formulation from Bio-Manguinhos (n = 36) or the biosimilar epoetin formulation (n = 38) in a double-blind fashion. The inclusion criteria were current epoetin therapy and stable hemoglobin levels for at least 3 months prior to the study. The primary and secondary outcomes were mean monthly hemoglobin levels and safety, respectively. The dose was calculated according to international criteria and adjusted monthly in both groups according to hemoglobin levels and at the assistant physicians' discretion. Iron storage was estimated at baseline and once monthly. Clinicaltrials.gov: NCT01184495. RESULTS: The study was conducted for 6 months after randomization. The mean baseline hemoglobin levels were 10.9±1.2 and 10.96±1.2 g/dL (p = 0.89) in the Bio-Manguinhos epoetin and biosimilar epoetin groups, respectively. During the study period, there was no significant change in hemoglobin levels in either group (p = 0.055, ANOVA). The epoetin from Bio-Manguinhos was slightly superior in the last 3 months of follow-up. The adverse event profiles of the two formulations were also similar. CONCLUSIONS: The epoetin formulations tested in this study are equivalent in efficacy and safety.